16. PHARMACISTS' KNOWLEDGE, ATTITUDES AND CHALLENGES TOWARDS COUNTERFEIT MEDICINE IN HO CHI MINH CITY: A CROSS-SECTIONAL STUDY (Vietnam Journal of Community Medicine, 2025)
Background: Counterfeit medicines (CFM) cause serious health consequences, increase economic and social burdens and affect the reputation of national health systems. Understanding the importance of pharmacists, their level of knowledge, attitude and challenges of CFM and influencing factors is essential for effective CFM prevention solutions.Objective: To survey pharmacists’ knowledge, attitudes and challenges on CFM in Ho Chi Minh City.Method: A cross-sectional study was conducted on 398 pharmacists in Ho Chi Minh City in December 2024. The study used an online survey questionnaire, attitudes and perspectives were responded to via a 5-point Likert scale, attitude questions were evaluated for consistency using Cronbach's alpha. Descriptive statistics and univariate regression analysis were used to analyze the data, with p < 0.05 indicating a statistical significance.Results: The majority of pharmacists (64.1%) had received any training on CFM. The main sources of information about CFM were their practice and the media (67.6%). The majority of pharmacists had knowledge and understanding of CFM, and the mean score of participants’ attitudes towards CFM was 19.1/25. Poor cross-border enforcement was considered a challenge in CFM prevention. Years of experience, previous training and pharmacy ownership influenced the mean score of pharmacist attitudes.Conclusion: The study revealed findings on pharmacists’ knowledge, attitude and challenges regarding CFM in Ho Chi Minh City. Strengthening the strength of the legal system along with close coordination of management agencies is an effective solution in preventing CFM.
Keywords: Attitudes; challenges; counterfeit medicine; Ho Chi Minh City; knowledge.